A Bioorthogonal‐Activated Fluorescence Turn‐On Probe Based on Nitrone‐Modified 1, 8‐Naphthalimide for Live‐Cell Imaging. Issue 2 (9th December 2021) - Teng, Yu; Yang, Hong; Li, Xiang; Wang, Yongcheng; Yin, Dali; Tian, Yulin
Comprehensive Summary: A nitrone‐modified 1, 8‐naphthalimide was designed as a novel bioorthogonal‐activated turn‐on probe based on strain‐promoted alkyne‐nitrone cycloaddition (SPANC). The bioorthogonal cycloadducts were subsequently transformed into fluorescent rearrangement products by photo‐acceleration, which exhibited significant fluorescence enhancement, large stokes shift, and high fluorescence quantum yield. DFT calculations were performed to elucidate the fluorescence OFF‐ON mechanism. This fluorogenic strategy was successfully applied to labeling of proteins and visualizing mitochondria in live cells in real time. Abstract : A nitrone‐modified 1, 8‐naphthalimide was synthesized as a novel bioorthogonal‐activated turn‐on probe based on strain‐promoted alkyne‐nitrone cycloaddition (SPANC), which can be successfully applied to labeling of proteins and visualizing mitochondria in live cells in real time.